2012
DOI: 10.1039/c1cc16647f
|View full text |Cite
|
Sign up to set email alerts
|

Pt(iv) analogs of oxaliplatin that do not follow the expected correlation between electrochemical reduction potential and rate of reduction by ascorbate

Abstract: In contrast to the Pt(IV) derivatives of cisplatin, Pt(IV) derivatives of oxaliplatin do not show the expected correlation between the electrochemical reduction potentials and rates of reduction by ascorbate. This is probably due to the lower ability of the amine and carboxylato ligands to form a bridge with the reducing agents to facilitate electron transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
195
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(219 citation statements)
references
References 19 publications
21
195
0
3
Order By: Relevance
“…They did not however suggest that GSH was the reducing agent [76][77][78]. Similarly, Nakai reported that when the cis-diamminetetrachlorido-platinum(II) complex was reduced by GSH, cisplatin-GSH adducts were formed that sequestered the cisplatin away from the DNA [79]. Dabrowiak noted that when oxoplatin and its carboxylate analog were reduced with GSH, cisplatin is not produced in the reaction medium.…”
Section: Reduction By Glutathionementioning
confidence: 94%
“…They did not however suggest that GSH was the reducing agent [76][77][78]. Similarly, Nakai reported that when the cis-diamminetetrachlorido-platinum(II) complex was reduced by GSH, cisplatin-GSH adducts were formed that sequestered the cisplatin away from the DNA [79]. Dabrowiak noted that when oxoplatin and its carboxylate analog were reduced with GSH, cisplatin is not produced in the reaction medium.…”
Section: Reduction By Glutathionementioning
confidence: 94%
“…There are a number of reports of the chemical reduction of Pt IV to Pt II , and it is widely accepted that a concerted twoelectron transfer from, for example, ascorbate, GSH, or guanine, to Pt IV is involved. [12,15] However, the photoreduction of 1 may not follow the above pathway. Pt IV is more likely to gain one electron from each of the two N 3 or two OH ligands and give rise to N 3 C or OHC radicals, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, these compounds are prodrugs that have to undergo extracellular or preferably intracellular reduction by agents like ascorbic acid, glutathione, or high molecular weight biomolecules, thereby resulting in the antitumor active square-planar platinum(II) metabolites. [24][25][26][27][28] Thus, the activity of these complexes depends on a range of bioinorganic and pharmacological attributes like the reduction potential, lipophilicity and solubility, binding behavior to biomolecules, and inertness with regard to ligand exchange reactions. [29][30][31] Several studies show that the type of axial ligands has an exceptionally high influence on the reduction potential and consequently on the cytotoxicity (chlorido ligands, high reduction potential and high cytotoxicity; hydroxido ligands, low reduction potential and low cytotoxicity).…”
Section: Introductionmentioning
confidence: 99%